Improvements in electric vehicle battery technology influence vehicle lightweighting and material substitution decisions. (1st February 2021) - Burd, Joshua Thomas Jameson; Moore, Elizabeth A.; Ezzat, Hesham; Kirchain, Randolph; Roth, Richard
Graphical abstract: Highlights: Global demand for and adoption of battery electric vehicles is on the rise. To achieve increased driving range, there is increased interest in lightweighting. Increased battery energy density and motor improvements can lower costs. As these costs decline, the need for high cost lightweight materials will diminish. Cost tradeoffs and technological advances can impact decision-making. Abstract: Demand for battery electric vehicles (BEVs) has grown over the past decade as a result of climate action targets and energy policies globally. To improve driving range and minimize battery costs, BEV manufacturers have adopted lightweight materials with the objective of reducing energy requirements and enabling the use of smaller, less expensive batteries. However, improvements in battery energy density and electric motor technologies have enhanced vehicle performance and lowered costs independently. Thus, the need for expensive lightweight materials for mass savings could diminish as these technologies rapidly advance. This study evaluates lightweight material substitution cost tradeoffs and their changes over time for an advanced high strength steel and aluminum BEV design. Process-based cost modeling methods assess cost tradeoffs for body and closures and mass scaling estimations inform costs in the battery and motor, chassis, and other vehicle systems. Under current conditions, a steel design costs $595 less per vehicle than aluminum, where steel's cost advantage is in body and closures manufacturing and aluminum's advantage is in battery, motor, and chassis manufacturing cost. As lightweighting advantages of battery and motor costs decline over time, the cost gap grows wider, with a $743 per vehicle cost advantage for steel. These results underscore the importance of accounting for technological advancements and learning when projecting BEV costs. This material substitution decision ultimately has implications for energy systems and long-term profitability of BEV business models. As BEV performance and costs improve, there will be an increase in demand for BEVs, electricity, and charging infrastructure.